ASPEK PERLINDUNGAN HUKUM PERJANJIAN DALAM JUAL BELI ONLINE MENURUT FIQH KONTEMPORER - Defriza, Rita (Prodi Hukum Ekonomi Syari'ah STAIN Mandailing Natal, 2020)
The form of buying and selling agreements has grown so rapidly as the effort to achieve the needs of human life, sometimes the agreement does not meet the provisions of the law, and can even occur imbalance. Likewise with E-commerce that generally includes the form of buying and selling, because it can not be denied fraud against the rights of others even the interests of the public in general. To address this matter, Islam has given guidelines to achieve the welfare of the community. Online or ecommerce trading is a transaction in the purchase and sale of goods and/or services through a potential source of information and technology by using a consumer service through a network of computers that surround the Internet in every internal transaction in an organization, so that online includes all electronic transactions. Contemporary scholars who argue that transactions with modern principles are valid on the condition that there is clarity in the transaction. Among them were Shaykh Muhammad Bakhit al Muthi'i, Mushthofa az Zarqa ', Wahbah Zuhaili and Abdullah bin Mani '.